The transitional states of a floating wind turbine during high levels of surge. (November 2022) - Kyle, Ryan; Früh, Wolf-Gerrit
Abstract: With the deployment of floating offshore wind turbines, the effect of their wind- and wave-induced platform motion on the turbine's performance and life is of concern and requires low-order models to develop appropriate control strategies. This work focusses on platform surge as one of the main additional degrees of freedom. The aerodynamic behaviour during the rotor's transition into propeller state is explored by assessing the spanwise and rotor-integrated aerodynamic forces on the rotor of the NREL 5 MW turbine through a 3D URANS CFD simulation. The CFD findings are compared with a modified actuator disk (AD) theory and 2D Blade-Element Momentum (BEM) approach. In addition to propeller state, where both rotor torque and thrust are negative, two other states were observed with opposite signs of torque and thrust: a braking state, with negative torque but positive thrust, and the second a quasi-windmill state with thrust negative yet torque positive. The results demonstrate that BEM coupled with AD can reliably predict the transitions to these states during such high levels of platform surge and give hints to how the underpinning force balances are affected by temporal perturbations. Highlights: Surging floating wind turbines can enter a succession of power and thrust states. A new quasi-windmill state has been found beyond propeller state. High-resolution CFD simulations have been used to develop a low-order model. The model is based on a modified actuator disk and blade element momentum theory. The model can be used to predict likelihood of states and magnitude of their impact.